A CLUSTER OF SARS‐COV‐2 DELTA VARIANT OF CONCERN ADDITIONALLY HARBORING F490S, NORTHERN LOMBARDY, ITALY. (March 2022) - Novazzi, Federica; Baj, Andreina; Pasciuta, Renee; Genoni, Angelo; Drago Ferrante, Francesca; Tripiciano, Rosalia; Catanoso, Giuseppe; Focosi, Daniele; Maggi, Fabrizio
Highlights: The Delta variant of concern (VOC) of SARS-CoV-2 has become dominant worldwide. We report a cluster caused by B.1.617.2 harboring the additional mutation of concern (MOC) F490S. The immune escape mutation F490S appears to impair vaccine efficacy. The immune escape mutation F490S is rapidly increasing in prevalence worldwide. Abstract: The Delta variant of concern (VOC) of SARS-CoV-2 has become dominant worldwide. In this article, we report a cluster caused by B.1.617.2 harboring the additional mutation of concern (MOC) F490S. We observed that 5 fully vaccinated subjects aged between 47 and 84 years were infected with this variant. The immune escape mutation F490S, first identified in the Lambda VOI, appears to impair vaccine efficacy and is rapidly increasing in prevalence worldwide.